2019
DOI: 10.1002/mabi.201900221
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Uptake of Gold Nanoparticles and Their Movement in 3D Multicellular Tumor Spheroids: Effect of Molecular Weight and Grafting Density of Poly(2‐hydroxyl ethyl acrylate)

Abstract: It is known that the size of gold nanoparticles (GNPs) is not the only determining factor in the uptake by cells such as cancer cells. The surface functionalization plays a crucial role, in particular the nature of the ligand as well as the molecular weight and the grafting density. Here, poly(2-hydroxy ethyl) acrylate (pHEA) with molecular weights ranging from 10, 20 to 39 g mol −1 via reversible addition-fragmentation chain transfer polymerization is synthesized. These polymers are used directly to coat GNPs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 60 publications
1
21
0
Order By: Relevance
“…An exploration of gold nanorods, nanospheres, and oligonucleotide-functionalized nanospheres was undertaken by Rane et al who showed the difference in uptake profiles present in a 3D model compared to the 2D monolayer [ 43 ]. Further studies on how functionalization and size of the GNPs have been explored recently, all agreeing that smaller GNPs will more effectively penetrate deeper into the cells [ 44 , 45 ]. More complex in vivo systems can also be reproduced in a spheroid model, such as a blood-brain barrier made up multiple cell types in a multicellular spheroid.…”
Section: Introductionmentioning
confidence: 99%
“…An exploration of gold nanorods, nanospheres, and oligonucleotide-functionalized nanospheres was undertaken by Rane et al who showed the difference in uptake profiles present in a 3D model compared to the 2D monolayer [ 43 ]. Further studies on how functionalization and size of the GNPs have been explored recently, all agreeing that smaller GNPs will more effectively penetrate deeper into the cells [ 44 , 45 ]. More complex in vivo systems can also be reproduced in a spheroid model, such as a blood-brain barrier made up multiple cell types in a multicellular spheroid.…”
Section: Introductionmentioning
confidence: 99%
“…There is limited information in the literature about how ECM inuences nanoparticle penetration into tumours. [6][7][8][9] This is partially due to the fact that most studies rely on complex animal models, especially human tumour xenogras. These models are expensive, time-consuming, and have been raising more ethical concerns.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, consideration of the effect of various curvatures on the colloid-surface interaction forces can help expand this technique to include various degrees of roughness and concave surfaces as well. However, only limited studies have been conducted to date on the adhesion of PGNs as a function of surface curvature [17][18][19].…”
Section: Introductionmentioning
confidence: 99%